2018
DOI: 10.7202/1051231ar
|View full text |Cite
|
Sign up to set email alerts
|

La Synergologie Révisée Par Les Pairs. Analyse D’une Publication

Abstract: Les partisans de la synergologie la considèrent comme une discipline scientifique. Mais l’unique publication révisée par les pairs (Turchet, 2013) comporte des lacunes (utilisation inadaptée de la littérature scientifique pour justifier les arguments, biais méthodologiques). Par ailleurs, des astuces rhétoriques sont utilisées afin de présenter certains résultats comme validant les hypothèses. Ainsi, la synergologie n’a que l’apparence d’une discipline scientifique et l’absence de théories et validations fiabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The Eye-Accessing Cues (EAC) model of NLP conveys the idea that the direction of non-visual eye movements appearing during internal cognition indicates the sensory system involved in the representation the person has in mind: for example, memory retrieval would be associated with a gaze looking up to the left ( Wiseman et al, 2012 ). Recent reviews, however, showed that the majority of the studies trying to replicate the postulates of the EAC model did not support it ( Diamantopoulos et al, 2009 ; Rochat et al, 2018 ). It is therefore a problem if the general public, not least scientists, have to refer to such pseudoscience when looking for the interpretation of gaze direction during social interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The Eye-Accessing Cues (EAC) model of NLP conveys the idea that the direction of non-visual eye movements appearing during internal cognition indicates the sensory system involved in the representation the person has in mind: for example, memory retrieval would be associated with a gaze looking up to the left ( Wiseman et al, 2012 ). Recent reviews, however, showed that the majority of the studies trying to replicate the postulates of the EAC model did not support it ( Diamantopoulos et al, 2009 ; Rochat et al, 2018 ). It is therefore a problem if the general public, not least scientists, have to refer to such pseudoscience when looking for the interpretation of gaze direction during social interactions.…”
Section: Introductionmentioning
confidence: 99%